2002
DOI: 10.1037/0882-7974.17.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on memory encoding in the frontal lobes.

Abstract: Functional magnetic resonance imaging (fMRI) was used to compare frontal-lobe activation in younger and older adults during encoding of words into memory. Participants made semantic or nonsemantic judgments about words. Younger adults exhibited greater activation for semantic relative to nonsemantic judgments in several regions, with the largest activation in the left inferior frontal gyrus. Older adults exhibited greater activation for semantic judgments in the same regions. but the extent of activation was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 66 publications
6
124
0
6
Order By: Relevance
“…In a functional MRI study (fMRI), Stebbins et al (2002) found less activation in left prefrontal cortex in older adults relative to younger adults while they carried out a single-word semantic judgment task. Using magnetoencephalography (MEG), Kemmotsu et al (2012) compared young to middle-aged adults (mean age of 50 years-old) during single-word semantic judgment task, and reported that middle-aged adults recruited the inferior prefrontal region to a lesser extent than young adults.…”
Section: Discussionmentioning
confidence: 99%
“…In a functional MRI study (fMRI), Stebbins et al (2002) found less activation in left prefrontal cortex in older adults relative to younger adults while they carried out a single-word semantic judgment task. Using magnetoencephalography (MEG), Kemmotsu et al (2012) compared young to middle-aged adults (mean age of 50 years-old) during single-word semantic judgment task, and reported that middle-aged adults recruited the inferior prefrontal region to a lesser extent than young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Cabeza et al, 2000;Logan et al, 2002;Morcom et al, 2003) and visuospatial (Grady et al, 1995(Grady et al, , 1998Kelley et al, 1998) information. In elders, reduction of left PFC activation has been linked to reduced performance (Stebbins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Simulating cognitive aging in younger adults by means of experimental manipulations (e.g., division of attention) has been a successful approach in behavioral studies (Ma¨ntyla¨and Ba¨ckman, 1992;Castel and Craik, 2003). The pharmacological approach proposed here would extend this research strategy to the neural level, and provide more mechanistic evidence pertaining to the role of DA neurotransmission in the age-differential patterns of brain activation often observed in functionalimaging studies (Rypma and D'Esposito, 2000;Rypma et al, 2001;Grady et al, 1995;Stebbins et al, 2002;Cabeza, 2002;Cabeza et al, 2002).…”
Section: Pharmacological Intervention Comt Genotype and Brain Activmentioning
confidence: 99%
“…By collecting PET-based DA data and functional-imaging data during task performance on the same individuals, several intriguing issues in the cognitive neuroscience of aging could be addressed. For example, in activation studies, an under-recruitment of task-relevant frontal regions has been associated with age-related deficits in tasks assessing working memory (Rypma and D'Esposito, 2000;Rypma et al, 2001) and episodic memory (Grady et al, 1995;Stebbins et al, 2002). In this context, it is of interest to note that several studies on DA and cognitive aging have used cognitively demanding tasks (e.g., executive tasks, episodic memory tasks) that have been shown to activate prefrontal regions in functional imaging studies (see Cabeza and Nyberg, 2000, for review).…”
Section: Da Imaging and Brain Activationmentioning
confidence: 99%